2012
DOI: 10.1097/nne.0b013e3182461be3
|View full text |Cite
|
Sign up to set email alerts
|

An End-of-Life Care Interdisciplinary Team Clinical Simulation Model

Abstract: To provide quality end-of-life care, nursing students must have clinical experiences participating on interdisciplinary teams. The authors present the structure and processes of a clinical simulation experience that help students embrace the importance of interdisciplinary collaboration in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…In considering the utility and validity of the Gabby et al (2014) pyramid approach, six of the studies do not include all three elements, although some of these studies have a limited report of the evaluation of the simulation learning (Fluharty et al, 2012;Gilliland et al, 2012;Leighton & Dubas, 2009;Pullen et al, 2012;Swenty & Eggleston, 2011;Tuxbury et al, 2012). The remaining 11 studies include elements of all three skills factors (technical, soft, and learning), which may support the view that Gabby et al's (2014) concept is a good fit as a frame for analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In considering the utility and validity of the Gabby et al (2014) pyramid approach, six of the studies do not include all three elements, although some of these studies have a limited report of the evaluation of the simulation learning (Fluharty et al, 2012;Gilliland et al, 2012;Leighton & Dubas, 2009;Pullen et al, 2012;Swenty & Eggleston, 2011;Tuxbury et al, 2012). The remaining 11 studies include elements of all three skills factors (technical, soft, and learning), which may support the view that Gabby et al's (2014) concept is a good fit as a frame for analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Only two studies reported none of the aspects of student learning (Barnato et al, 2008;Pullen et al, 2012). The other reviewed studies identified that students recognized simulation as an acceptable and suitable learning experience.…”
Section: Learning Skillsmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of interprofessional collaboration in health care environments is widely acknowledged in the literature as being necessary in improving patient outcomes internationally (Pullen, et al 2012) and is described as being essential to ensure safe, effective patient-centred and collaborative care (Blue & Zoller, 2012). Interprofessional care is important in all health care settings, however, interprofessional care is especially important and often challenging in the provision of palliative and end-of-life care where a range of health care professionals are involved in providing care, not only to the dying patient, but to the patient's significant others.…”
Section: Interprofessional Education and Healthcare (Ipe)mentioning
confidence: 99%
“…Finally, the study by Pullen et al (2012), from the USA, using several interactive teaching methods, including simulation, reports primarily on involvement of associate degree nursing students (n=140), and 25 students from the allied health professions who participated in classroom and clinical simulation experiences. In this study it is unclear which allied health students participated.…”
Section: Interprofessional Palliative Care and End-of-life Care Simulmentioning
confidence: 99%